2022
DOI: 10.1007/s11064-022-03806-7
|View full text |Cite
|
Sign up to set email alerts
|

Munc18-1 Contributes to Hippocampal Injury in Septic Rats Through Regulation of Syntanxin1A and Synaptophysin and Glutamate Levels

Abstract: Sepsis-associated encephalopathy (SAE) is a diffuse brain dysfunction closely associated with mortality in the acute phase of sepsis. Abnormal neurotransmitters release, such as glutamate, plays a crucial role in the pathological mechanism of SAE. Munc18-1 is a key protein regulating neurotransmission. However, whether Munc18-1 plays a role in SAE by regulating glutamate transmission is still unclear. In this study, a septic rat model was established by the cecal ligation and perforation. We found an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The abundance of synaptic glutamate can excessively activate NMDAR, thus resulting in excitotoxicity and subsequent harm to nerve cells ( Asada et al, 2022 ). The research has shown that CLP rats exhibit elevated levels of glutamate in the hippocampus, in conjunction with an upregulated expression of the NMDAR1 glutamate receptor ( Tang et al, 2023 ). Syntaxin1A primarily serves as an indicator for synaptic vesicles abundance in synaptically active regions ( Ullrich et al, 2015 ).…”
Section: Pathogenesis Of Sepsis-associated Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of synaptic glutamate can excessively activate NMDAR, thus resulting in excitotoxicity and subsequent harm to nerve cells ( Asada et al, 2022 ). The research has shown that CLP rats exhibit elevated levels of glutamate in the hippocampus, in conjunction with an upregulated expression of the NMDAR1 glutamate receptor ( Tang et al, 2023 ). Syntaxin1A primarily serves as an indicator for synaptic vesicles abundance in synaptically active regions ( Ullrich et al, 2015 ).…”
Section: Pathogenesis Of Sepsis-associated Encephalopathymentioning
confidence: 99%
“…Additionally, the expression levels of Syntaxin1A, synapsin and glutamate decreased after interference with Munc18-1 siRNA. These indicated that Munc18-1 may affect glutamate levels by regulating Syntaxin1A and synapsin, thereby participating in the process of hippocampal injury in septic rats ( Tang et al, 2023 ).…”
Section: Pathogenesis Of Sepsis-associated Encephalopathymentioning
confidence: 99%